2012
DOI: 10.4102/phcfm.v4i1.294
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of People living with HIV and AIDS attending the Antiretroviral Clinic, University College Hospital, Nigeria

Abstract: BackgroundQuality of life (QOL) is an important component in the evaluation of the well-being of people living with HIV and AIDS (PLWHA), especially with the appreciable rise in longevity of PLWHA. Moreover, limited studies have been conducted in Nigeria on how PLWHA perceive their life with the World Health Organisation Quality of Life Brief Scale (WHOQOL-Bref) instrument.ObjectiveThis study assessed the QOL of PLWHA attending the antiretroviral (ARV) clinics, UCH Ibadan, Nigeria.MethodA cross-sectional study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
48
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 15 publications
13
48
2
1
Order By: Relevance
“…8 In a study conducted by Folasire et al in Nigeria in 2008, the mean age of the respondents was 38.1±9.0 years. 9 This confirms that most of the HIV cases occur among the sexually active and economically productive population who are responsible for child bearing and bread winning for the family. Hence this problem results in economic loss to the country.…”
Section: Socio Demographic Factorssupporting
confidence: 55%
See 2 more Smart Citations
“…8 In a study conducted by Folasire et al in Nigeria in 2008, the mean age of the respondents was 38.1±9.0 years. 9 This confirms that most of the HIV cases occur among the sexually active and economically productive population who are responsible for child bearing and bread winning for the family. Hence this problem results in economic loss to the country.…”
Section: Socio Demographic Factorssupporting
confidence: 55%
“…14 In a study Folasire et al, found mean QOL score was similar in male and female. 9 Nirmal et al in their study found women had lower mean QOL score than men, patients with better educational background had higher QOL score. Patients with lower CD4count has significantly lower QOL score.…”
Section: Factors Affecting Qolmentioning
confidence: 88%
See 1 more Smart Citation
“…These items are distributed in four domains which include: physical, psychological, social and environmental. In calculating the QoL, the mean score of each item is converted to a scale of 0 to 100, where 100 was considered the highest QoL [12]. Venous blood (5 ml) each was then collected from each patient and healthy control into a plain test tube for biochemical analysis and EDTA (with anticoagulant) tube for immunological assays.…”
Section: Subjects and Study Designmentioning
confidence: 99%
“…Also, in Bangladesh, it was discovered that majority of the patients were with low QOL in all domains (Imam et al, 2011). Studies in Nigeria by Fatiregun et al (2009) in Kogi State, Odili et al (2011) in Benin City, Folasire et al (2012) in Ibadan and Bello et al (2013) in Ilorin reported poor QOL in social and environmental domains of patients on cART. Most of these earlier studies were not followed with interventions to enhance patients' QOL.…”
Section: Introductionmentioning
confidence: 98%